Relevansi Pemikiran Pendidikan Ki Hajar Dewantara dalam Konteks Sistem Pendidikan Nasional di Indonesia - Wahyu Sihab; Mukhsin Achmad (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2025)
This research discusses Ki Hajar Dewantara's concept of educational thought, focusing on character education and the formation of students' personalities, as well as the challenges and opportunities in integrating this thought into the national education system. Ki Hajar Dewantara emphasized the importance of liberating education, namely education that does not only focus on intellectual aspects, but also on the formation of students' character as a whole so that they become independent, noble, and highly motivated individuals. In the current context of national education, Ki Hajar Dewantara's ideas are still relevant, but their implementation faces various challenges, such as a dense curriculum, lack of in-depth understanding among educators, and the dominance of cognitive approaches in schools. However, there are also great opportunities to integrate Ki Hajar Dewantara's educational values through curriculum reform, training for educators, and the application of holistic learning methods. This study concludes that the integration of Ki Hajar Dewantara's thoughts into the national education system can be a strong foundation for building a generation that is not only intelligent, but also has character, provided that the existing challenges can be overcome with a comprehensive approach.